Compute $E((B_t−1)^2\int ^t_0(B_s+1)^2 dB_s)$ for $t≥0$ given that $(B_t)_{t≥0}$ is a Standard Brownian Motion.

Presume we will need to compute $E((B_t+B_s)-(B_s-1))^2$ to get some independent terms but really stuck on what to do with the integral part. Thanks for any help with this question.

  • $\begingroup$ @Did could you clarify why $E(B_{t}X_{t})=E(\int_0^tY_{s}ds)$. $\endgroup$ – Zugzwangerz Jan 10 at 15:35

Consider the processes $$X_t=\int ^t_0Y_s dB_s\qquad Y_t=(B_t+1)^2$$ By repeated applications of Itô isometry, one gets:

  • $E(X_t)=0$
  • $B_tX_t=\displaystyle\int_0^tdB_s\cdot\int ^t_0Y_sdB_s$ hence $$E(B_tX_t)=E\left(\int_0^tY_s ds\right)=\int_0^tE(Y_s)ds$$
  • $(B_t^2-t)X_t=\displaystyle\int_0^t2B_sdB_s\cdot\int ^t_0Y_sdB_s$ hence $$E((B_t^2-t)X_t)=E\left(\int_0^t2B_sY_s ds\right)=2\int_0^tE(B_sY_s)ds$$

Finally, if one can compute $E(Y_t)$ and $E(B_tY_t)$, the proof is complete. Can you?

  • $\begingroup$ Like at every other step, use Itô isometry, based on the fact that $$d\langle B,B\rangle_t=dt$$ hence, for every suitable processes $(u_t)$ and $(v_t)$, $$E\left(\int_0^tu_sdB_s\cdot\int_0^tv_sdB_s\right)=E\left(\int_0^tu_sv_sds\right)$$ $\endgroup$ – Did Jan 10 at 15:38
  • $\begingroup$ ((This is answering a comment formerly here but now on main, by the OP.)) $\endgroup$ – Did Jan 10 at 15:38
  • $\begingroup$ ah I get it now, thank you! $\endgroup$ – Zugzwangerz Jan 10 at 15:39

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.